Synthesis and reactivity of magnetically diverse Au@ Ni core-shell nanostructures - Bharathan, Vysakh A.; Raj, Govind K.; Joy, Pattayil Alias; Vinod, Chathakudath P. (Particle & Particle Systems Characterization, 2014)
Core-shell bimetallic Au@Ni nanoparticles, with gold cores and thin nickel shells with overall size less than 10 nm, are synthesized and stabilized in pure cubic (fcc) and hexagonal (hcp) phase. Due to their unique crystal, electronic, and geometric structure, they show interesting magnetic and chemical properties. The Au@Ni-fcc is magnetic, whereas Au@Ni-hcp is non-magnetic. Both the bimetallic nanostructures are stable to surface oxidation until 150 degrees C and show excellent catalytic activity for p-nitrophenol reduction reaction.
Keywords: Au-Ni nanoparticles; bimetallic nanostructures; magnetic core-shell nanoparticles; oxidation resistance

Synthesis of Au@Ni bimetallic core shell nanoparticle and nanochains in soyabean oil and their catalytic hydrogenation reactions - Bharathan, Vysakh A.; Yadukiran, V.; Lazar, Anish; Singh, Anand. P.; Vinod, Chathakudath P. (ChemistrySelect, 2016)
Synthesis of Au@Ni bimetallic core shell nanostructures using commercially available soya bean oil as the solvent through a sequential reduction strategy is reported. The energy efficiency and economic viability comes from the much milder temperatures and replacement of expensive and environmentally hazardous solvents like long chain organic amines and acids previously reported for synthesis. Thus, core shell nanoparticles having size regime of 10-15 nm with an excellent control over the nickel shell thickness (2 nm) over the gold core (8-10 nm) and Au@Ni nanochains is achieved. The synthesized materials are demonstrated to synergistically catalyze hydrogenation of nitro and C-C multiple bonds with much better efficiency as compared to individual nanoparticle counterparts.
Keywords: Bimetallic nanoparticles; Gold catalysis; hydrogenation reactions; synergistic effects

Diverse reactivity trends of Ni surfaces in Au@Ni core-shell nanoparticles probed by near ambient pressure (NAP) XPS - Bharathan, Vysakh A.; Jain, Ruchi; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Science & Technology, 2017)
A mild temperature sequential reduction method in aqueous medium is reported for the synthesis of Au@Ni nanoparticles with a core-shell morphology. The nickel shell thickness with a gold core in the nanostructure can be tuned from 2 nm up to about 10 nm. Near ambient pressure XPS (NAPXPS) studies under oxygen atmosphere show that Au-80@Ni-20 with an extremely thin nickel shell (similar to 2 nm) follows a distinctly different decomposition pathway of metastable Ni(OOH) species compared to those with larger shell thickness which behave more like individual nickel surfaces. Thus, Ni(OOH) on Au-80@Ni-20 decomposes to metallic Ni at 100 degrees C and is found to resist oxidation at 0.1 mbar oxygen at this temperature. Those with a larger nickel shell thickness behave more like monometallic Ni in terms of their decomposition and oxidation properties. The Au@Ni system with an ultra thin metallic nickel overlayer (2 nm) shows high catalytic activity and selectivity for phenylacetylene hydrogenation under mild conditions which outweighs their monometallic counterparts and those with higher nickel shell thickness.